The effect of zinc fertilization on the yield and element content of ryegrass - Kremper, Rita; Seres, László (Acta Agraria Debreceniensis, 2010)
The effect of Zn fertilization on the yield and Zn, N, P, K, Mg and Mn content of ryegrass was studied in a greenhouse experiment for 8 chernozem soils with three replicates under uniform NPK supply and irrigation. The applied Zn rates were 0, 2.5 and 5 mg/kg Zn. Due to Zn doses the yield incrased significantly. Zn fertilization increased the plant Zn content and decreased the plant P and Mn content significantly. For N, K and Mg there was no significant effect.